ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BRAND LOYALTY PADA AGEN TRAVEL ONLINE DI KOTA BATAM - Jihan Karisma; Suyono Saputra (FEB Universitas Sam Ratulangi Manado, 2023)
The growing development of technology can lead to competition between entrepreneurs in the field of tourism, precisely in online travel as a Traveloka, Agoda, Booking.com etc and the increasing number of competitors creates intense competition and causes travel entrepreneurs to compete to provide quality and the best services for consumers using sophisticated systems and technology that will produce online travel companies. to be better, in this study the author has its own meaning, namely to identify things that can have an impact related to the variables brand satisfaction, brand image, brand value, perceived quality, perceived value as independent variables and brand trust as intervening variables and brand loyalty as dependent variables. The researcher's analysis suggests that this study obtained a total of 319 respondents and used a quantitative analysis method using the SPSS and Smart PLS applications. no significant effect. Furthermore, direct testing shows that the only significant variables are brand trust-brand loyalty and perceived value-brand trust and in indirect testing that the only significant variable is Perceived Value -> Brand Trust -> Brand Loyalty. keywords : Brand satisfaction, Brand image, Brand value, Perceived quality, Brand perceived value, Brand trust, Brand loyalty